2011
DOI: 10.5372/1905-7415.0504.067
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication (Original). Preparation of a novel porous scaffold from poly(lactic-co-glycolic acid)/hydroxyapatite

Abstract: Background: Scaffolds for bone tissue engineering must meet functional requirements, porosity, biocompatibility, and biodegradability. Different polymeric scaffolds have been designed to satisfy these properties. Composite materials could improve mechanical properties compared with polymers, and structural integrity and flexibility compared with brittle ceramics. Objective: Fabricate poly (lactic-co-glycolic acid) (PLGA) /hydroxyapatite (HA) porous scaffolds by freezeextraction method, and evaluate the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Moreover, small intestinal mucosa SIS‐loaded PLGA scaffolds were prepared by solvent casting/particle leaching (Kim et al ., ); bone formation on an SIS–PLGA hybrid scaffold as a natural–synthetic scaffold was better than that on a PLGA‐only scaffold. Moreover, the important role of HA was evaluated by seeding scaffolds with MSCs in vitro (Nazarpak et al ., ; Yun et al ., ; Zhang and Chen, ) and in vivo (He et al ., ; Kim et al ., ), showing a significant increase in bone formation in terms of mineralization and expression of bone‐specific genetic markers. PLGA scaffold chemical modification could also be possible with a mixture of fibrin and hyaluronic acid (HY) (Kang et al ., ): fibrin/HY used as a vehicle for drug delivery coating of the scaffold significantly enhanced initial cell attachment and in vitro release of BMP‐2; the transplantation of undifferentiated ADCs inoculated on BMP‐2‐loaded, fibrin/HY‐coated scaffolds resulted in a more improved bone formation and mineralization.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…Moreover, small intestinal mucosa SIS‐loaded PLGA scaffolds were prepared by solvent casting/particle leaching (Kim et al ., ); bone formation on an SIS–PLGA hybrid scaffold as a natural–synthetic scaffold was better than that on a PLGA‐only scaffold. Moreover, the important role of HA was evaluated by seeding scaffolds with MSCs in vitro (Nazarpak et al ., ; Yun et al ., ; Zhang and Chen, ) and in vivo (He et al ., ; Kim et al ., ), showing a significant increase in bone formation in terms of mineralization and expression of bone‐specific genetic markers. PLGA scaffold chemical modification could also be possible with a mixture of fibrin and hyaluronic acid (HY) (Kang et al ., ): fibrin/HY used as a vehicle for drug delivery coating of the scaffold significantly enhanced initial cell attachment and in vitro release of BMP‐2; the transplantation of undifferentiated ADCs inoculated on BMP‐2‐loaded, fibrin/HY‐coated scaffolds resulted in a more improved bone formation and mineralization.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…For a material to be used as a scaffold or a template for bone repair, it often needs to have biocompatibility, biodegradability and holes suitable for cell growth. Figure 3a shows the preparation of the degradable material poly(lactic-co-glycolic acid)/hydroxyapatite after the processes of water ultrasonication, refrigeration and air-drying [19]. The morphology result showed that the average pore diameter was 50 mm, which is larger than the 10 mm required for cell infiltration as verified by cell experiments in vitro [21].…”
Section: Physical Propertiesmentioning
confidence: 92%